DIAGNOSIS OF HYPOVITAMINOSIS IN RABBITS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Annotation: This article describes the changes in clinical signs of the etiopathogenesis of hypovitaminoses in rabbits,the effects of vitamin premixes and probiotics. The importance of probiotics and their properties in rabbit hypovitaminoses, as well as the efficacy of vitamin premixes and probiotics in coadministration, have been demonstrated.